A novel maleic acid/graphite composite anode for lithium ion batteries with high energy and power density. (June 2018) - Wang, Yan; Zheng, Xueying; Qu, Qunting; Liu, Gao; Battglia, Vincent S.; Zheng, Honghe
Abstract: Herein, a maleic acid/graphite composite is prepared as the anode of lithium ion batteries. Compared to the traditional graphite electrode, the maleic acid/graphite composite electrodes exhibit much improved electrochemical performances in terms of reversible capacity, rate capability and cycling stability. At a current density of 40 mA g −1, a reversible capacity of 1067.3 mAh g −1 is obtained. Even at an extremely high current density of 8 A g −1, a capacity of 889.0 mAh g −1 is retained. The composite electrode is still able to deliver 989.1 mAh g −1 capacity after 1000 cycles at 400 mA g −1 current density, manifesting excellent cycling stability. Mechanisms for the high electrochemical performances of the maleic acid/graphite composite anode are discussed. Reversible lithiation/de-lithiation of the maleic acid nanoballs contributes high capacity to the composite electrode. The mitigated volume expansion of the graphite by the flexible organic material explains the excellent cycling stability of the composite electrode. Graphical abstract: Image 1